HIF-1 inhibition reverses opacity in a rat model of galactose-induced cataract. - Masaru Takashima; Masaya Nagaya; Yoshihiro Takamura; Masaru Inatani; Masaya Oki (PLoS ONE, 2024)
Cataract is an eye disease, in which the lens becomes opaque, causing vision loss and blindness. The detailed mechanism of cataract development has not been characterized, and effective drug therapies remain unavailable. Here, we investigated the effects of Hypoxia-inducible factor 1 (HIF-1) inhibitors using an ex vivo model, in which rat lenses were cultured in galactose-containing medium to induce opacity formation. We found that treatment with the HIF-1 inhibitors 2-Methoxyestradiol (2ME2), YC-1, and Bavachinin decreased lens opacity. Microarray analysis on 2ME2-treated samples, in which opacity was decreased, identified genes upregulated by galactose and downregulated by inhibitor treatment. Subsequent STRING analysis on genes that showed expression change by RT-qPCR identified two clusters. First cluster related to the cytoskeleton and epithelial-mesenchymal transition (EMT). Second cluster related to the oxidative stress, and apoptosis. ACTA2, a known marker for EMT, and TXNIP, a suppressor of cell proliferation and activator of apoptosis, were present in each cluster. Thus, suppression of EMT and apoptosis, as well as activation of cell proliferation, appear to underlie the decrease in lens opacity.